Determination of Flow Direction and Catchment Area Model Using Quantum GIS Analysis and Remote Sensing Imagery at Nickel Mining Locations - Syarifudin, Erick; Chaerul, Muhammad; Gusty, Sri (ASTONJADRO, 2025)
The research location is located at IUP PT. IFISHDECO, Tbk (122.168° - 122.204° East Longitude (BT) and 4.371° - 4.404° South Latitude (LS), Tinanggea, South Konawe Regency, Southeast Sulawesi Province.. The study aims to determine the surface flow direction and catchment area model at nickel mining sites. The data is in the form of topographic data measured with a total station, by conducting spatial analysis with Quantum GIS (QGIS) and remote sensing with the Strahler method in determining the river network. The results of research conducted at the research location obtained 3 catchment areas, namely Catchment 1 covering an area of 19,021 Ha, catchment 2 covering an area of 32,691 Ha and Catchment 3 covering an area of 59.77 Ha which can be used in further analysis in the mining drainage system.